Effect of solid-to-liquid ratios on the properties of waste catalyst–metakaolin based geopolymers. (30th July 2015) - Cheng, Hui; Lin, Kae-Long; Cui, Rong; Hwang, Chao-Lung; Cheng, Ta-Wui; Chang, Yu-Min
Highlights: WCMBG samples contained 10% waste catalyst exhibited greater compressive strength and lower porosity. Geopolymer samples were filled the pores, thus leading to the formation of a denser structure. WCMBG samples showed the major structures of the Si and Al are Q 4 (3Al) and Q 4 (2Al). The porosity of a WCMBG increases with the level of waste catalyst replacement. We report effect of solid-to-liquid ratios of waste catalyst–metakaolin based geopolymers. Abstract: In this study, the changes caused by adding a waste catalyst on the properties of the final product were investigated by applying curing on samples of waste catalyst metakaolin-based geopolymers (WCMBGs) prepared with different solid-to-liquid (S/L) ratios (0.66–0.81) and at different waste catalyst replacement levels (0–40 wt.%). The mechanical properties of WCMBG samples, such as compressive strength and porosity, were determined after the curing process. Thermogravimetric and differential thermal analysis (TG/DTA), 29 Si magic-angle spinning nuclear magnetic resonance ( 29 Si MAS NMR), and scanning electron microscopy (SEM) were also used to determine their microstructural properties. When the S/L ratio was 0.76, WCMBG samples contained 10% waste catalyst exhibited greater compressive strength and lower porosity which were comparable with pure metakaolin samples. The TG/DTA results indicated that WCMBG samples contained 10 wt.% waste catalyst had more structural water and geopolymer gels. The results of 29 Si NMR spectroscopy of the samples showed that the major structures of the Si and Al are Q 4 (3Al) and Q 4 (2Al), and strong resonances were between −85 and −95 ppm, respectively. Furthermore, the waste catalyst was the compromising resource material in preparing geopolymers.